The role of organizational culture in the quality of banking service financial perspective Applied research in a sample of Iraqi private banks - سعيد عبد السلام لفتة; حلو سناء حسن (Journal of Economics and Administrative Sciences, 2017)
The banking sector is a cornerstone of the national economy because of its large role of economic development of a country, which requires the advancement of this vital sector and interest in all the accompanying changes to him in order to survive and grow and continue Accordingly dealt Find reversal (organizational culture, on the quality of banking service ) sought search to achieve a number of cognitive and practical goals by selecting (10), especially among the working banks in Iraq Iraqi banks and the period is the surveyed period (2005-2014) embodied the research problem in the dialectical relationship between the (organizational culture) and its impacts on banking service quality. Through a set of questions to reach the effect of each variable of variables in the quality of banking services and access to the most influential indicators have been formulating hypotheses President reflect the link and influence between the variables in question to achieve the aim of the research and mutual relationship between research variables and the statement of the most important relationships necessary and a statement morale out the results of the influence of independent variables on the dependent variable according to statistical tests used for this purpose. The researcher recommends the need to adopt such changes in the banking research and dissemination of the community as they have a major role in achieving the quality of banking services.